Effects of different equilibration duration, vapour exposure temperature and vapour exposure duration on the sperm freezability of Thai mahseer (Tor tambroides) / Shahrulzaman Shaharuddin - Shahrulzaman, Shaharuddin (2011)
The experiment was carried out to determine the effects of equilibration duration, vapour exposure temperature and vapour exposure duration in sperm cryopreservation protocol for Tor tambroides fish using modified Fish Ringer Extender (FRE); and subsequently used in experiment to develop optimal combination of equilibration duration, vapour exposure temperature and vapour exposure duration. Also, an experiment was performed to compare the frozen-thawed sperm characteristics between low temperature incubator and normal refrigerator during cryopreservation process; and the results have been utilised for subsequent final experiment in attempt of the transfer of technology from laboratory to the field condition for the sperm cryopreservation of Tor tambroides under field condition. The freezing process under laboratory ambient was conducted in freezing laboratory, ISB Mini Farm (Livestock), University of Malaya in which a total of 20 Thai mahseer male fish was involved. The freezing process under field condition was carried out in Taman Negara Sg. Relau (Merapoh), Pahang which included a total of 17 Thai mahseer male fish. The mature Thai mahseer males were induced hormonally by injection of Ovaprim (0.5 ml/kg) 24 hours before the milt collection process. Semen was collected by gentle squeezing using centrifuge tube. The collected semen was diluted with Fish Ringer Solution (FRS) at 1:10 ratio after which was mixed with DMSO (10% of the diluent). The mixture was loaded into the 0.25/0.50 ml French straws and sealed. Subsequently the freezing process was carried out and stored in liquid nitrogen tank. Straws were thawed in water bath at 30ºC for 1 minute for evaluation of the sperm. Sperm motility characteristics for frozen-thawed sperm were evaluated using an Automated Semen Analyzer (IVOS, Hamilton-Thorne). The effect of factors and parameters were statistically analysed using one-way ANOVA and Duncan Multiple Range Test (DMRT). Duration of 30 minutes equilibration gave higher total motility (67.31±1.27%) than 45 and 60 minutes (61.93±1.31% and 65.09±1.02%, respectively) durations for Thai mahseer sperm cryopreservation protocol. Among three temperatures used for vapour exposure phase in this study, -110°C was considered to be the most suitable temperature which obtained the highest values in total motility and progressive motility (68.53±1.13% and 15.75±0.61%, respectively) compared to -100°C (60.74±1.41% and 11.65±0.68%, respectively) and -120°C (65.07±0.99% and 12.56±0.56%, respectively). Meanwhile, 15 minutes of vapour exposure duration produced the highest values of total motility and progressive motility (65.25±1.25% and 14.83±0.71%, respectively) compared to 5 (63.87±1.31% and 12.31±0.58%, respectively) and 10 minutes durations (65.21±1.09% and 12.82±0.58%, respectively). Combination of 30 minutes of equilibration duration, -110°C of vapour exposure temperature and 10 minutes of vapour exposure duration; combination of 30 minutes of equilibration duration, -110°C of vapour exposure temperature and 15 minutes of vapour exposure duration; and combination of 30 minutes of equilibration duration, -120°C of vapour exposure temperature and 15 minutes of vapour exposure duration were considered as three optimal combinations in sperm cryopreservation of Thai mahseer and were used in subsequent experiment. Combination of 30 minutes of equilibration duration, -110°C of vapour exposure temperature and 15 minutes of vapour exposure duration showed the highest values in total motility and progressive motility (72.80±2.85% and 21.20±4.02%, respectively) compared to other two combinations [(72.40±2.27% and 16.80±2.22%, respectively) and (70.80±2.35% and 18.20±2.48%, respectively)] used. Both low temperature incubator and normal refrigerator attained the same effect during the equilibration phase which showed no significant differences when using all equilibration durations (30, 45 and 60 minutes) in total motility (ranging from 97.07±0.74% to 97.60±0.50%, from 87.80±1.74% to 88.40±1.59% and from 88.33±1.59% to 88.67±1.87%, respectively) and progressive motility (ranging from 34.60±4.04% to 38.60±4.16%, from 23.13±2.16% to 23.93±2.95% and from 21.13±1.83% to 21.47±2.48%, respectively) values. As for comparison, the freezing process under laboratory ambient produced higher values in total motility, progressive motility, rapid, medium, slow and ALH (75.03±1.49%, 19.47±1.46%, 24.80±1.83%, 10.23±0.74%, 38.53±1.52% and 3.26±0.12 μm, respectively) compared to freezing process under field condition (35.81±1.69%, 8.96±0.64%, 10.36±0.75%, 4.76±0.37%, 23.11±1.36% and 2.95±0.10 μm, respectively). However, the most interesting facts from this attempt, there were no significant differences in VAP, VSL, VCL, BCF, STR and LIN values between the freezing under laboratory ambient and field condition with a range from 41.54±0.91 μm/s to 43.53±1.33 μm/s, from 37.24±0.90 μm/s to 38.10±1.28 μm/s, 57.30±0.95 μm/s to 61.16±1.35 μm/s, from 24.96±0.62 Hz to 25.48±1.04 Hz, from 86.33±0.53% to 87.94±0.44% and from 62.03±1.20% to 62.93±0.69%, respectively. In summary, the results demonstrate that the Thai Mahseer sperm could be cryopreserved using modified Fish Ringer Extender (mFRE) with good frozen-thawed sperm motility characteristics both under laboratory ambient as well as field condition.